Chapter 8 Discourse on LGBTQ issues in the Polish presidential campaign (2020) The perception of the LGBTQ community and foreign media - Barczyszyn-Madziarz, Paulina (Taylor & Francis, 2022)
Gender, Politics, Elections, Democracy, LGBTQ